PTH-027 Location and kudo pit pattern reflect neoplastic histology of lesions detected at surveillance colonoscopy in inflammatory bowel disease. (17th June 2017) - Iacucci, M; Akinola, O; Panaccione, R; Kaplan, G; Leung, Y; Novak, K; Seow, C; Gui, X; Urbanski, S; Minoo, P; Lethebe, B; Lowerison, M; et al.
Abstract : Introduction: Effective colonoscopic surveillance of IBD benefit from having reliable predictors of neoplasia, since targeted biopsies and endoscopic resection are increasingly used as standard of practice. It is not clear whether Kudo pit patterns may be applicable in characterising IBD associated lesions. We aimed to identify the specific clinical and endoscopic features of colonic lesions which predict dysplasia in IBD. Method: All lesions identified in a randomised study to determine the detection rates of neoplastic lesion (NL) in patients with long standing colitis in IBD ( NCT02098798 ) were included. NL were classified by the Paris classification, Kudo pit pattern, and by the Vienna classification. Univariate analysis was performed, and age, duration of disease, extra-intestinal manifestations, family or personal history of polyps/cancer, smoking, size of lesion, Paris classification, Kudo pit pattern, localization/extension were considered .Subsequently a multivariate logistic regression model analyses was created and analysed with candidate variables which had p values≤0.05 on univariate analysis. Results: A total of 270 patients (55% men; median age 49y) were assessed by High Definition (n=90), virtual chromoendoscopy (n=90) or dye chromoendoscopy (n=90). Among 270 patients, ninety- one (33.7%) colonic dysplastic lesions and 1 adenocarcinoma were found. Sixty–two (68.8%) were polypoid and twenty-nine (31.8%) were non polypoid. Most of these lesions (92.3%) had Kudo pit pattern III-V. By univariate analysis, age- Odds Ratio (OR) 1.05 (95% CI:1.02–1.08), localization of the lesions in the right colon- OR 6.15 ( 95% CI: 3.12–12.12), Kudo pit pattern IIO, III-IV and V- OR 20.91 (95% CI:9.34–46.7) and Paris Is/Ip classification OR- 3.29 (95% CI 1.69–6.38) were associated with NL. Subsequently proportional multivariate logistic regression model for the prediction of colonic neoplasia confirmed that the endoscopic Kudo pit pattern- OR 21.50 (95% CI:86.5–60.1) and localization of the lesions in the right colon- OR 6.52 (95% CI:1.98–22.5) were predictors of colonic neoplasia at surveillance colonoscopy in IBD (Table). The overall accuracy of independent variables which predict neoplastic histological changes was 78% (95% CI 68%–88%), sensitivity 82% (95% CI 68%–97%), specificity 68% (95% CI 47%–89%), PPV 85% (95% CI 76%–95%) and NPV 64% (95% CI 42%–86%) which were significant in the multivariate analysis. Conclusion: We demonstrated that the endoscopic Kudo pit pattern and localization of the lesions in the right colon were predictors of neoplasia in IBD. This may guide management strategy of NL detected at IBD surveillance. Disclosure of Interest: M. Iacucci Conflict with: Pentax, O Akinola: None Declared, R Panaccione: None Declared, G Kaplan: None Declared, Y Leung: None Declared, K Novak: None Declared, C Seow: None Declared, X Gui: None Declared, S Urbanski: None Declared, P Minoo: None Declared, B Lethebe: None Declared, M Lowerison: None Declared, S Ghosh: None Declared